Opportunity Cost and the Incidence of a Draft Lottery - Paul Bingley; Petter Lundborg; Stéphanie Vincent Lyk-Jensen (Institute for the Study of Labor (IZA), 2014)
Military conscription implicitly taxes draftees. Those who would have volunteered at the market wage may be forced to serve for lower wages, and those with higher opportunity costs may be forced to serve regardless, yet little is known about the distribution of this burden. We exploit the Danish draft lottery to estimate the causal effect of military service on labor earnings of young men across the cognitive ability distribution. We find that high ability men who are induced to serve face a 7 percent earnings penalty, whereas low ability men face none. Educational career disruption is an important channel.
Keywords: J24; J31; J45; 330; conscription; military service; earnings; draft lottery